Investigating mechanisms underlying neurodevelopmental phenotypes of autistic and intellectual disability disorders: a perspective - Kroon, Tim; Sierksma, Martijn; Meredith, Rhiannon M. (Frontiers in Systems Neuroscience, 2013)
Brain function and behaviour undergo significant plasticity and refinement, particularly during specific critical and sensitive periods. In autistic and intellectual disability neurodevelopmental disorders (NDDs) and their corresponding genetic mouse models, impairments in many neuronal and behavioural phenotypes are temporally regulated and in some cases, transient. However, the links between neurobiological mechanisms governing typically normal brain and behavioural development (referred to also as ‘neurotypical’ development) and timing of NDD impairments are not fully investigated. This perspective highlights temporal patterns of synaptic and neuronal impairment, with a restricted focus on autism and intellectual disability types of NDDs. Given the varying known genetic and environmental causes for NDDs, this perspective proposes two strategies for investigation: (1) a focus on neurobiological mechanisms underlying known critical periods in the (typically) normal-developing brain (2) investigation of spatio-temporal expression profiles of genes implicated in monogenic syndromes throughout affected brain regions. This approach may help explain why many NDDs with differing genetic causes can result in overlapping phenotypes at similar developmental stages and better predict vulnerable periods within these disorders, with implications for both therapeutic rescue and ultimately, prevention.